Evaluation of compositional and engineering properties of offshore Venezuelan soils. Volume 2, North of Paria stiff clays / by Charles C. Ladd, Aziz M. Malek, R. Torrence Martin, Rami Mishu. - Ladd, Charles C. (Charles Cushing); Malek, Aziz Moussa.; Martin, Robert T.; Mishu, Rami.; INTEVEP, S.A.; Massachusetts Institute of Technology. Department of Civil Engineering. Constructed Facilities Division. (Tufts University. Tisch Library., 2019)
1 online resource (217 pages) : illustrations.; "Prepared for Instituto Technologico Venezolano del Petroleo."; "Geotechnical order no. 706."; "MIT/Instituto Technologico Venezolano del Petroleo Offshore Research and Development Program"--Cover.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.